Manajemen Program Keluarga Harapan (PKH) dan Program Indonesia Pintar (PIP) Dalam Meningkatkan Layanan Pendidikan Dasar - Sobari; Nana Suryapermana; Moch. Muizuddin (Formosa Journal of Social Sciences (FJSS), 2022)
The purpose of this study was to describe the participation and knowledge of the people of Waringin Kurung Serang District about the Hopeful Family Program and the Smart Indonesia Program, to describe the contribution of the Management of the Hopeful Family Program Management of the smart Indonesian program in improving basic education services in the Waringin Kurung Serang District and to know the positive and negative impacts. generated by the two programs. This research is a qualitative descriptive study with data collection methods; interviews, observations and documentation. Meanwhile, the data analysis was carried out using a gap analysis model (servQual analysis), covering the stages of design, installation, process, product, management and cost as well as inhibiting and supporting factors. The results of this study indicate that the participation of the Waringin Kurung community in participating in this program has existed since these two programs were launched, namely in 2014. Meanwhile, the knowledge of beneficiary families about PKH and PIP is sufficient in terms of substance and benefits. The contribution that the Hope Family Management can make in improving students' basic education services, especially for beneficiary families, is to reduce the family's economic burden, reduce the number of children dropping out of school, raise students' learning motivation, improve student achievement and psychologically this assistance is able to increase student confidence. The positive impacts include reducing the family's economic burden, increasing children's motivation and achievement. While the negative impacts that arise are; the emergence of social jealousy between those who receive and those who do not, the program assistance is mistargeted in its use, the emergence of dependence on assistance.